Gratitude Letter: An Effort to Increase Subjective Well-Being in College - Stefanus Arista Christanto; Dea Brenda; Clara Assisiansi; Maria Jessica Pangestu; Ignatia Sarita; Vania Sulistiani (ANIMA Indonesian Psychological Journal, 2017)
A preliminary study of students of a psychology faculty, revealed the fact that there are some students with low life satisfaction and negative affect during their college life. Low subjective well-being (SWB) was associated with decreased productivity and cognitive flexibility, which are important elements for studying. Previous researchers found a significant correlation between gratitude and SWB. The aim of this study is to enhance student SWB through an intervention of gratitude letter. We use two stages in this study: first a descriptive method (N = 282) to have an accurate description of the level of their SWB. Then, we select 60 students with the lowest SWB to participate in the next stage, a quasi-experimental method with multiple group design, consisting of two experimental group and one control group. Measurements were conducted with modified SLS, SPANE, and GQ6. Data a-nalysis revealed significant differences in gratitude and positive affect level that are differrent in each group. Significant improvement in gratitude and subjective well-being based on the pre-test, post-test 1, post-test 2 were only found in the group that writes and expresses the gratitude letter.